Pattern of Exchange Rate Distributions - Anton Abdulbasah Kamil (Program Studi Statistika Unisba, 2007)
This analysis is conducted within the contect of a stochastic version of the Dornbusch (1976)overshooting model, following the Miller and Weller (1991) extension of Krugman (1991), with shocksto aggregate supply. Hence, three realistic features are added to the Krugman (1991) model: (i) homeand foreign products are imperfect substitutes in consumption so that purchasing power parity isrelaxed, (ii) prices and wages are sluggish, and (iii) there are intra marginal as well as infra-marginalinterventions in the foreign exchange market. The objective of this paper is thus to show that meanreversion introduced by sluggish adjustment of prices and wages combined with a degree of intramarginalintervention can result in a hump-shaped exchange rate distribution and thereby explainthe empirical evidence. We would like to show that the hump shape is more likely to occur when thedegree of monetary accommodation is close to what is needed to peg the nominal exchange rate (sothat the fundamental has to move far away from its mean for the exchange rate to reach itsboundaries).